Optimizing Service Quality: The Role of Human Resources Development at Gunungsitoli City's Central Statistical Agency - Juita Telaumbanua; Eliyunus Waruwu; Eliagus Telaumbanua; Forman Halawa (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to clarify the impact of human resource development on service quality at the Central Statistics Agency of Gunungsitoli City. Utilizing qualitative methods, the study collects secondary data through interviews with a focus on human resource development. The analysis reveals that human resource development significantly influences the quality of services provided by the government in Gunungsitoli City. Specifically, the findings indicate that improved human resources lead to enhanced performance of government personnel, thereby positively affecting service quality. This study underscores the critical role of effective human resource development in elevating organizational performance and service delivery.